Depression Affected by Burns Injury: A Narrative Literature Review - Irwansyah Irwansyah (HM Publisher, 2021)
Burn-related pain during surgical procedures and physical rehabilitation is associated with anxiety, and studies have shown that procedural pain-associated anxiety increases as therapy progresses. This literature review aimed to describe depression-related burn injuries. Burn scars often lead to disfigurement, potentially causing an altered body image, lack of adequate social functioning, and poor quality of life for the patient. Subjective body image dissatisfaction is an essential predictor of post-burn psychological functioning 12 months post-injury. Psychiatric problems are pervasive in burn survivors. A range of psychological problems, such as anxiety, depression, low self-esteem, and trauma-related disorders, can occur in these patients. The severity of burns, total body surface area involved, site of burns, and burn depth all have a role in developing psychiatric problems. Social and environmental factors may also play a part in the genesis of psychiatric sequelae. In conclusion, burn patients should be routinely screened for psychiatric morbidity, and that all cases be assessed by a psychiatrist at least once during their inpatient stay. Sensitization of the burns ward staff to the patient's psychological needs is equally important.